2009
DOI: 10.1161/hypertensionaha.108.125914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth Parameters on Retinal Vascular Caliber

Abstract: Abstract-Recent studies reported an association between smaller birth size and narrower retinal vascular caliber, but it remains unclear whether this association is attributed to confounding by shared environment or genetic factors. At a mean age of 9.3 years, 266 twins (49 monozygotic and 84 dizygotic pairs) in the Twins Eye Study in Tasmania underwent an ophthalmic examination including retinal photography. Retinal vascular caliber was measured using a validated protocol. The majority of these twins were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
4
34
2
1
Order By: Relevance
“…We are aware of only one other study that reports recall of birth length, which showed accurate recall but only 6–10 weeks after delivery (Troude et al, 2008). Birth length has been demonstrated to be an independent predictor for various health outcomes (Maehle et al, 2010; Melve et al, 2000; Sun et al, 2009), and may actually serve as a better indicator of birth size than birth weight (Silva et al, 2008). Thus, while there may be growing interest in obtaining this information, our finding highlights the need for researchers to use caution when relying on maternal reports of birth length.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only one other study that reports recall of birth length, which showed accurate recall but only 6–10 weeks after delivery (Troude et al, 2008). Birth length has been demonstrated to be an independent predictor for various health outcomes (Maehle et al, 2010; Melve et al, 2000; Sun et al, 2009), and may actually serve as a better indicator of birth size than birth weight (Silva et al, 2008). Thus, while there may be growing interest in obtaining this information, our finding highlights the need for researchers to use caution when relying on maternal reports of birth length.…”
Section: Discussionmentioning
confidence: 99%
“…As described elsewhere (39, 44), all of the twins had 10° stereoscopic optic disc–centered photographs using a Nidek 3-Dx/F fundus camera (Nidek) after dilatation of the pupils with tropicamide 1% or cyclopentolate 1%. Photographs were digitalized, and retinal vessel caliber was measured with computer-assisted software (IVAN, University of Wisconsin, USA) according to a standardized protocol (45).…”
Section: Methodsmentioning
confidence: 99%
“…Estimates were summarized as the central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE), representing the average caliber (diameter) of arterioles and venules of the eye, respectively, using a revised Knudtson-Parr-Hubbard formula (46). Reliability of the retinal vessel measurement has been published elsewhere (44). Intragrader variation was assessed in 67 randomly selected retinal photographs.…”
Section: Methodsmentioning
confidence: 99%
“…In a sample of 1,369 young children, Mitchell et al [68 ]found that the mean retinal arteriolar caliber was narrowed by 2 µm per 1 kg reduction in birth weight. Data from the Twin Eye Study in Tasmania also showed that children who were born small had smaller mean retinal arterioles [69]. In contrast, previous data from the Singapore Cohort Study of the Risk Factors for Myopia and the Avon Longitudinal Study indicated that neither low birth weight nor preterm birth was associated with narrowed retinal arterioles [70,71].…”
Section: Determinants Of Retinal Vascular Calibersmentioning
confidence: 99%